Two Flavonoid Compounds as Antiproliferative Activity Against SP-C1 Cancer Tongue Cells from the Leaves of Rasamala (Altingia excelsa Nornha) - Risyandi Anwar; Arlette Setiawan; Supriatno Supriatno; Unang Supratman (Syarif Hidayatullah State Islamic University, 2018)
Two flavonoid compounds, kaempferol (1) and quercetin (2) have been isolated from the leaves of Rasamala (Altingia excelsa Nornha). The chemical structure of compounds 1 and 2 were identified by spectroscopic evidences including, UV, IR, 1D-NMR, 2D-NMR and MS as well as by comparing with previously reported spectral data.These compounds were isolated from this plant for the first time. Compounds 1 and 2 were evaluated for their antiproliferative activity against SP-C1 cancer tongue cells and showed IC50 values of 2.50 and 2.31 mM, respectively.